Pemanfaatan Google Classroom dan Video Pembelajaran berbasis Problem Solving sebagai Solusi Kegiatan Belajar Mengajar di Era Pandemi Covid-19 - Luthfiana Tarida; Indriyani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Akademi Maritim Nusantara Cilacap, 2020)
Covid-19 virus has an impact on changing learning patterns in Indonesia. The government invests in schools and lectures, but instructs them to continue teaching without face-to-face learning. Such learning requires the help of technological media that can be accessed anywhere. This is in line with the industrial revolution 4.0 which required educators and learners to use technology media in education. The media selected in this article are Google Classroom and Video Learning. The utilization of both media was applied to several courses at Akademi Maritim Nusantara Cilacap, among them applied mathematics and accounting and taxation of shipping companies. The materials in the learning video are presented in the form of problems, such as linear interpolation materials and budgeting. Therefore, it is necessary to plan and prepare material that is constructivism, so that cadets can play an active role. The material is presented on a problem solving basis, stimulating cadets to solve problems and then construction the concept of problem solving results. Utilization of Google Classroom equipped with Problem Solving-based Learning Video can be an alternative solution to online learning in the Covid-19 Pandemic Era. This is because educators and students do not need to come face-to-face. Students can access Google Classroom and learning videos with the help of PC/mobile devices and internet networks, without meeting in person, thus minimizing the increase in Covid19 sufferers.